2009
DOI: 10.1007/s11999-009-1009-1
|View full text |Cite
|
Sign up to set email alerts
|

Are BMPs Involved in Normal Nerve and Following Transection?: A Pilot Study

Abstract: Bone morphogenic proteins (BMPs) may have neurotrophic functions but there is limited evidence of these functions in the peripheral nervous system. We therefore investigated the expression of BMPs and BMP receptors (BMPRs) in normal and injured peripheral nerves. In 10 of 15 Sprague-Dawley rats, a 3-mm segment of sciatic nerve was resected at the trifurcation in the thigh. One day (n = 5) and 7 days (n = 5) after transection, proximal and distal stumps were removed and immunohistochemically analyzed for BMP-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…We found no evidence for a major developmental defect in sensory neurons in RGMb KO mice, and our data show that deletion of RGMb leads to impaired DRG neurite outgrowth in vitro and axonal regeneration in vivo . These data are in keeping with previous studies showing BMP involvement in these phenomena (Tsujii et al, 2009; Zou et al, 2009). Injury-induced axonal growth was shown to require the function of the BMP signaling effector Smad1.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found no evidence for a major developmental defect in sensory neurons in RGMb KO mice, and our data show that deletion of RGMb leads to impaired DRG neurite outgrowth in vitro and axonal regeneration in vivo . These data are in keeping with previous studies showing BMP involvement in these phenomena (Tsujii et al, 2009; Zou et al, 2009). Injury-induced axonal growth was shown to require the function of the BMP signaling effector Smad1.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, BMP receptors, ligands, and downstream effectors are expressed in the PNS, and there is an injury-induced regulation of these BMP-signaling pathway components (Ai et al, 1999; Tsujii et al, 2009; Zou et al, 2009). Interestingly, BMP signaling appears to have differential effects on neurite extension and axonal growth in the central (Matsuura et al, 2007; Matsuura et al, 2008; Liu et al, 2009) and peripheral (Hodge et al, 2007; Moon and Birren, 2008; Tsujii et al, 2009) nervous systems, BMP pathway activation appears to be predominantly inhibitory in the CNS and permissive in the PNS.…”
Section: Introductionmentioning
confidence: 99%
“…19 BMPs have been shown to be expressed in normal peripheral nerves regulating neuronal function, and BMP signaling appears activated upon peripheral nerve damage, suggesting that BMPs play a role in the peripheral nerve's response to injury. 20 …”
Section: Heterotopic Ossificationmentioning
confidence: 99%
“…Several studies support the theory that the stimulation of nerve regeneration is induced by the upregulation of endogenous BMP-2 expression and BMP signaling [39,40]. It has been suggested that exogenous application of BMP-2 may further promote axonal regeneration after peripheral nerve injury by regulation of neurotrophic factors, such as the nerve growth factor and the glial cell line-derived neurotrophic factor [18,37,41,42]. According to Ma et al [40], endogenous levels of BMPs are sufficient for enabling normal axonal growth and no further growth is produced by increasing BMP signaling above basal levels.…”
Section: Discussionmentioning
confidence: 91%
“…Evidence suggests that BMPs may be involved in neuronal regeneration and axonal growth through an injury-induced signaling regulation with BMP pathway activation being predominantly permissive in the peripheral nervous system and inhibitory in the central nervous system [18][19][20][21]. In a dog model of lumbar spine laminectomy defect, Meyer et al [22] reported the safety of rhBMP-2.…”
Section: Introductionmentioning
confidence: 99%